The Recovery of Muscle Spindle Sensitivity Following Stretching Is Promoted by Isometric but Not by Dynamic Muscle Contractions - Budini, Francesco; Rafolt, Dietmar; Christova, Monica; Gallasch, Eugen; Tilp, Markus (Frontiers in Physiology, 2020)
It is often suggested that stretching-related changes in performance can be partially attributed to stretching-induced neural alterations. Recent evidence though shows that neither spinal nor cortico-spinal excitability are susceptible of a long-lasting effect and only the amplitude of stretch or tap reflex (TR) is reduced up to several minutes. Since afferents from muscle spindles contribute to voluntary muscle contractions, muscle stretching could be detrimental to muscle performance. However, the inhibition of muscle spindle sensitivity should be reversed as soon as the stretched muscle contracts again, due to α-γ co-activation. The present work evaluated which type of muscle contraction (static or dynamic) promotes the best recovery from the inhibition in spindle sensitivity following static stretching. Fifteen students were tested for TR at baseline and after 30s maximal individual static stretching of the ankle plantar flexors followed by one of three randomized interventions (isometric plantar flexor MVC, 3 counter movement jumps, and no contraction/control). Ten TRs before and 20 after the procedures were induced with intervals of 30s up to 10 minutes after static stretching. The size of the evoked TRs (peak to peak amplitude of the EMG signal) following stretching without a subsequent contraction (control) was on average reduced by 20% throughout the 10 minutes following the intervention and did not show a recovery trend. Significant decrease in relation to baseline were observed at 9 of the 20 time points measured. After MVC of plantar flexors, TR recovered immediately showing no differences with baseline at none of the investigated time points. Following 3 counter movement jumps it was observed a significant 34.4% group average inhibition (p<0.0001) at the first time point. This effect persisted for most of the participants for the next measurement (60s after intervention) with an average reduction of 23.4% (p=0.008). At the third measurement, 90s after the procedure, the reflexes were on average still 21.4% smaller than baseline, although significant level was not reached (p=0.053). From 120 s following the intervention, the reflex was fully recovered. This study suggests that not every type of muscle contraction promote a prompt recovery of a stretch-induced inhibition of muscle spindle sensitivity.